Riboflavin for COVID-19 Adjuvant Treatment in Patients With Mental Health Disorders: Observational Study - Akasov, R. A.; Khaydukov, E. V.; Andreyuk, D. S.; Sholina, N. V.; Sheremeta, A. N.; Romanov, D. V.; Kostyuk, G. P.; Panchenko, V. Ya.; Kovalchuk, M. V. (Frontiers in Pharmacology, 2022)
Background: COVID-19 treatment remains a challenge for medicine because of the extremely short time for clinical studies of drug candidates, so the drug repurposing strategy, which implies the use of well-known and safe substances, is a promising approach. Objective: We present the results of an observational clinical study that focused on the influence of riboflavin (vitamin B2) supplementation on the immune markers of COVID-19 severity in patients with mental health disorders. Results: We have found that 10 mg of flavin mononucleotide (a soluble form of riboflavin) intramuscularly twice a day within seven days correlated with the normalization of clinically relevant immune markers (neutrophils and lymphocytes counts, as well as their ratio) in COVID-19 patients. Additionally, we demonstrated that total leucocytes, neutrophils, and lymphocytes counts, as well as the neutrophils to leucocytes ratio (NLR), correlated with the severity of the disease. We also found that patients with organic disorders (F0 in ICD-10) demonstrated higher inflammation then patients with schizophrenia (F2 in ICD-10). Conclusions: We suggest that riboflavin supplementation could be promising for decreasing inflammation in COVID-19, and further evaluation is required. This observational clinical trial has been registered by the Sverzhevsky Research Institute of Clinical Otorhinolaryngology (Moscow, Russia), Protocol No. 4 dated 05/27/2020.